PERAN KONTEN TIKTOK @VMULIANA SEBAGAI KEBUTUHAN INFORMASI MAHASISWA AKHIR - Saputra, Rendi; Yuliani, Fitria (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2024)
This research aims to analyze the role of @vmuliana TikTok content as a source of information for students. TikTok is a social media application that is popular among the younger generation, including students. Vina Muliana, a content creator on TikTok, shares educational content regarding job vacancy information, tips for making CVs, interview processes, BUMN and CPNS recruitment, as well as developing academic and non-academic skills. Through this content, Vina Muliana plays an important role in meeting the information needs of students, especially final year students who are looking for work or preparing to enter the world of work. The research results show that @vmuliana's TikTok content is a source of information, inspiration and motivation for students in developing their careers and skills. This research provides insight into the potential of social media, especially TikTok, in supporting students' information needs Keywords: TikTok Content, Information Needs, Final Students